Overcoming job demands to deliver high quality of care in the hospital setting across Europe: the role of teamwork and positivity - Costa, P. (2015)
Health care professionals deal on a daily basis with several job demands – emotional, cognitive, organizational and physical. They must also ensure high quality care to their patients. The aim of this study is to analyse the impact of job demands on quality of care and to investigate team (backup behaviors) and individual (positivity ratio) processes that help to shield that impact. Data was collected from 2,890 doctors and nurses in 9 European countries by means of questionnaires. Job demands have a negative impact on the quality of care delivered by health professionals. Backup behaviors had a mediating effect between job demands and quality of care. Also, the positivity ratio of professionals (ratio of positive and negative emotions experienced) was also found as a significant mediator between most job demands and quality of care dimensions. Finally, we found a double mediation between most job demands and quality of care, where backup behaviors influenced the positivity ratio. Quality of care in hospitals is closely related to job demands. Hospital managers should consider the importance of cooperation within health care professionals’ teams and ought to find ways to develop teamwork in order to promote patients’ safety.